Human Breast Milk: From Food to Active Immune Response With Disease Protection in Infants and Mothers - Lokossou, Gatien A. G.; Kouakanou, Léonce; Schumacher, Anne; Zenclussen, Ana C. (Frontiers in Immunology, 2022)
Breastfeeding is associated with long-term wellbeing including low risks of infectious diseases and non-communicable diseases such as asthma, cancer, autoimmune diseases and obesity during childhood. In recent years, important advances have been made in understanding the human breast milk (HBM) composition. Breast milk components such as, non-immune and immune cells and bioactive molecules including cytokines/chemokines, lipids, hormones, enzymes; reportedly play many roles in breastfed newborns and in mothers, by diseases protection and shaping newborn´s immune system. Bioactive components in HBM are also involved in tolerance and appropriate inflammatory response of breasfed infants if necessary. This review summarizes the current literature on the relationship between mother and her infant through breast milk with regard to disease protection. We will shed some light on the mechanisms underlying the roles of breast milk components in the maintenance of both child and mother’s health.